Attitudes Towards Wind Power in Northern Sweden : A Study to Examine the Importance of Compensation for Increased Acceptance to Establishment of Wind Power - Broström, Maria; Salomonsson, Nils Jon (2015)
The overall purpose of this study was to examine the factors that are of importance to local people for making them accept or not accept wind power in their community (with special focus on the importance of monetary compensation to the municipality). This was achieved by investigating if the individuals’ acceptance to a wind farm in the archipelago increased if the compensation to those who would be affected increased. It also aimed to see what factors influence these attitudes. The method chosen to achieve this was; the Contingent Valuation Method (CVM) through the means of a questionnaire survey. The total number of responses received was 149, of which 77 were with an example of low compensation and 72 of them were with a high compensation. The econometric model used to estimate the attitudes was the binary logit model. The results showed that in general, the inhabitants of Kalix were in favor of a future wind farm development on Bergön, where the beneficial properties of wind power for the environment and knowledge that a development would create jobs and revenue to the municipality, was factors that made individuals support wind power on Bergön. Validerat; 20150922 (global_studentproject_submitter)